Impact Of Economic Issues On Tax Compliance Of Income Tax Assesses In Haryana; A Behavioral Analysis (Journal of Namibian Studies : History Politics Culture, 2023)
The Income tax is a direct tax imposed on the gross total income of an individuals. In India, income tax is implemented under income tax act, 1961. The aim of implementing income tax was to enhance tax revenue generation for the development activities and equalisation in the society. Consequently, academics, academicians, and policymakers have been paying attention to the assessment of taxpayers' compliance with economic issues and income tax system. The objective of our study was to evaluate the level compliance with economic issues among income tax assesses in Haryana, as well as to analyze the impact of economic issues factors simplified tax rates, penalties &punishments, social security net, equitable taxation, fairness and transparency on tax compliance. We have specifically targeted the population from all division of Haryana state, 13 districts. We collected responses from 410 sample units using a semi-structured questionnaire and purposive sampling. We employed descriptive statistics, EFA, CFA and ordinary logistic regression model as our chosen analysis approaches. The findings indicate that simplified tax structure, penalties & punishments shows the impact on tax compliance behaviour of income tax assesses. The policy implication of the study is that the government should make simplify the tax structure and reduce the penalties and punishments of income tax in order to enhance their compliance with income tax regulations.